2015
DOI: 10.1007/s00270-015-1246-5
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Guided Percutaneous Biopsy of Mediastinal Masses Using a Large Bore Magnet: Technical Feasibility

Abstract: MRI-guided mediastinal biopsy is a safe procedure with high diagnostic accuracy, which may offer a non-ionizing alternative to CT guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…In three patients, major pneumothorax occurred requiring therapy by a chest tube. With respect to technical success, diagnostic yield and complication rate associated with CT fluoroscopy-guided percutaneous core needle biopsies of mediastinal masses, our study agrees with other similar studies [ 3 , 5 , 6 , 11 , 12 , 14 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. For instance, de Margerie-Mellon et al reported a technical success rate of 100% and a diagnostic yield of 87% in 285 consecutive patients which is one of the largest studies on this subject.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In three patients, major pneumothorax occurred requiring therapy by a chest tube. With respect to technical success, diagnostic yield and complication rate associated with CT fluoroscopy-guided percutaneous core needle biopsies of mediastinal masses, our study agrees with other similar studies [ 3 , 5 , 6 , 11 , 12 , 14 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. For instance, de Margerie-Mellon et al reported a technical success rate of 100% and a diagnostic yield of 87% in 285 consecutive patients which is one of the largest studies on this subject.…”
Section: Discussionsupporting
confidence: 91%
“…A variety of more or less invasive methods are used for obtaining biopsies of mediastinal lesions, such as open surgical procedures, video-assisted thoracoscopic surgery (VATS), transbronchial biopsy, cervical mediastinoscopy and image-guided percutaneous needle biopsy [ 2 ]. Percutaneous image-guided core needle or Tru-Cut biopsy of mediastinal masses is usually performed under computed tomography, sonography and magnetic resonance imaging guidance, allowing detailed visualization of the lesion and the adjacent mediastinal structures as well as precise localization and documentation of the biopsy needle [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a technical point of view, several different studies have highlighted the feasibility and advantages of MRIguidance for procedures performed in soft tissues [9]. In particular, MRI allows perfect visualisation of both the target area (tumour and surrounding organs) and the ice Table 1 IT metastases-related data Procedure Lesion Size Moreover, MRI offers multi-planar, real-time guidance enabling precise lesion targeting; and when needed, hydrodissection can be easily achieved and monitored under MRI-guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of MRcompatible devices include a 16-G MR-compatible coaxial needle (Wanlin Medical, Qingdao, China), 20 a 16-G titanium alloy MR-compatible sheath (CoaxNeedle; Invivo Germany GmbH, Schwerin, Germany) 17,25 as well as a 16-G MR-compatible coaxial puncture needle (Somatex Medical, Teltow, Germany) used together with an 18-G MR-compatible semiautomatic biopsy needle (Somatex Medical). 26 Fine-needle aspiration biopsies were performed using an 18-G coaxial MR-compatible titanium alloy sheath (Coax Needle; InVivo Germany GmbH) together with a 20-G MR-compatible titanium Chiba needle (MReye; Cook Medical Bloomington, IN). 16,18 The acquisition of MR images can heat up biopsy needles through RF-induced heating.…”
Section: Mr-compatible Equipmentmentioning
confidence: 99%